Outcomes in Open Reduction and Internal Fixation of Tarsometatarsal (Lisfranc) Injuries: A Contemporary Review of Fixation Constructs - Adrian J. Talia BBiomed, MD (Distinct.), MS, DipSurgAnat, FRACS (Orth.), FAOrthA; Sasha Roshan-Zamir MBBS (Hons), FRACS (Orth.), FAOrthA; David W. Shepherd BSc (Hons), MBBS, FRACS (Orth.), FAOrthA (Foot & Ankle Orthopaedics, 2025)
Visual Abstract This is a visual representation of the abstract.